Echocardiographic and Biochemical Factors Predicting Arrhythmia Recurrence After Catheter Ablation of Atrial Fibrillation—An Observational Study - Charitakis, Emmanouil; Karlsson, Lars O.; Papageorgiou, Joanna-Maria; Walfridsson, Ulla; Carlhäll, Carl-Johan (Frontiers in Physiology, 2019)
Background: RFA is a well-established treatment for symptomatic patients with AF. However, the success rate of a single procedure is low. We aimed to investigate the association between the risk of recurrence of atrial fibrillation (AF) after a single radiofrequency ablation (RFA) procedure and cardiac neurohormonal function, left atrial (LA) mechanical function as well as proteins related to inflammation, fibrosis, and apoptosis. Methods and Results: We studied 189 patients undergoing RFA between January 2012 and April 2014, with a follow-up period of 12 months. A logistic regression analysis was performed to investigate the association between pre-ablation LA emptying fraction (LAEF), MR-proANP, Caspase-8 (CASP8), Neurotrophin-3 (NT3), and the risk for recurrence of AF after a single RFA procedure. 119 (63.0%) patients had a recurrence during a mean follow-up of 402 ± 73 days. An increased risk of recurrence was associated with: Elevated MR-proANP (fourth quartile vs. first quartile: HR, 2.80 (95% CI, 1.14–6.90]; P = 0.025); Low LAEF (fourth quartile vs. first quartile: hazard ratio [HR], 2.41 [95% CI, 1.01–5.79]; P = 0.045); Elevated CASP8 (fourth quartile vs. first quartile: HR 12.198 95% CI 2.216–67.129; P = 0.004); Elevated NT-3 (fourth quartile vs. first quartile: HR 7.485 95% CI 1.353–41.402; P = 0.021). In a receiver operating characteristic curve analysis, the combination of MR-proANP, CASP8, and NT3 produced an area under the curve of 0.819; CI 95% (0.710–0.928). Conclusions: Patients with better LA mechanical function and lower levels of atrial neurohormones as well as of proteins related to fibrosis and apoptosis, have a better outcome after an RFA procedure. Unique identifier: No. NCT01553045 (https://clinicaltrials.gov/ct2/show/NCT01553045?term=NCT01553045&rank=1).